The Influence of Intellectual Capital and Environmental Performance on Company Value with Financial Performance as an Intervening Variable in Manufacturing Companies - Ni Kadek Aprina Asriani; Desak Nyoman Sri Werastuti; Anantawikrama Tungga Atmadja (Jurnal Ilmiah Akuntansi, 2024)
This research aims to examine the influence of intellectual capital and environmental performance on firm value, with financial performance as an intervening variable, in manufacturing firms. The study focuses on manufacturing companies listed on the Indonesia Stock Exchange (BEI), with samples selected based on specific criteria. Data analysis is conducted using SEM-PLS (Structural Equation Modeling-Partial Least Squares) with Smart PLS software version 3.0. The results reveal that intellectual capital positively and significantly impacts both financial performance and firm value. However, environmental performance does not significantly influence financial performance or firm value. Additionally, financial performance does not significantly impact firm value and does not mediate the relationship between intellectual capital, environmental performance, and firm value. These findings suggest that while intellectual capital directly enhances financial performance and firm value, environmental performance does not play a significant role in influencing these outcomes, and financial performance does not serve as a mediator in these relationships.